Bisphenol S favors hepatic steatosis development via an upregulation of liver MCT1 expression and an impairment of the mitochondrial respiratory system. Issue 7 (13th May 2022) - Mornagui, Bessem; Rezg, Raja; Repond, Cendrine; Pellerin, Luc
Abstract: Bisphenol S (BPS) is a common substitute of bisphenol A (BPA). Recent data suggest that BPS acts as an obesogenic endocrine disruptor with emerging implications in the physiopathology of metabolic syndrome. However, the effects of BPS on monocarboxylate transporters (acting as carriers for lactate, pyruvate, and ketone bodies) and the mitochondrial respiratory system in the liver remain limited. For this purpose, male Swiss mice were treated with BPS at 100 µg/kg/day for 10 weeks, in drinking water. An increase in body weight and food intake was observed with no increase in locomotor activity. Moreover, data show that BPS increases hepatic MCT1 (a key energetic fuel transporter) mRNA expression accompanied by hepatic steatosis initiation and lipid accumulation, while disrupting mitochondrial function and oxidative stress parameters. Furthermore, BPS produced a significant increase in lactate dehydrogenase and creatine kinase activities. We can suggest that BPS contributes to hepatic steatosis in mice by upregulating monocarboxylate transporters and affecting the bioenergetic status characterized by an impaired mitochondrial respiratory system. Thus, our data highlight a new mechanism putatively implicated in hepatic steatosis development during BPS‐induced obesity involving lactate metabolism. Abstract : Bisphenol S (BPS) could increase hepatic lactate uptake via MCT1 activation leading to lipid accumulation and hepatic steatosis in mice. Indeed, we suggest that MCT1 induction can induce an increase in the ATP/ADP ratio that will decrease AMPK phosphorylation leading to enhanced activation of the transcription factor sterol regulatory element‐binding protein (SREBP1) that induces different pathways causing lipid accumulation in the liver. Also, BPS causes an impairment of hepatic mitochondrial function and an oxidative stress which could alter energy metabolism and more precisely lactate influx and oxidation. More investigations are needed to highlight BPS‐induced steatosis and its associated complications.